Release of prednisolone and inulin from a new calcium‐alginate chitosan‐coated matrix system for colonic delivery. Issue 8 (9th July 2013) - Araujo, Valeria; Gamboa, Alexander; Caro, Nelson; Abugoch, Lilian; Gotteland, Martin; Valenzuela, Fernando; Merchant, Hamid A.; Basit, Abdul W.; Tapia, Cristián
Abstract: Putative colonic release formulations of calcium (Ca)‐alginate coated with chitosan containing two different actives, prednisolone and inulin, were prepared in three different sizes, beads ( D 50 = 2104 μm) and microparticles ( D 50 = 354 and 136 μm). The formulations were tested in standard phosphate buffer and biorelevant Krebs bicarbonate buffer at pH 7.4, and were further evaluated in the presence of the bacterium E . coli . Product yield and encapsulation were higher with prednisolone than with inulin. In Krebs bicarbonate buffer, a clear relationship between particle size and prednisolone release was observed. In contrast, release of inulin was independent of the particle size. In phosphate buffer, the particles eroded quickly, whereas in Krebs buffer, the particles swelled slowly. The difference in behavior can be attributed to the formation of calcium phosphate in the phosphate buffer medium, which in turn weakens the Ca‐alginate matrix core. In the presence of E. coli, the formulations were fermented and the release of prednisolone was accelerated. In conclusion, the buffer media affects formulation behavior and drug release, with the bicarbonate media providing a better simulation of in vivo behavior. Moreover, the susceptibility of the formulations to bacterial action indicates their suitability as carriers for colonic drug delivery. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:2748–2759, 2013